Antioxidant activity of Nigella sativa Seeds Aqueous Extract and its use for cryopreservation of buffalo spermatozoa. (26th April 2018) - Awan, M. A.; Akhter, S.; Husna, A. U.; Ansari, M. S.; Rakha, B. A.; Azam, A.; Qadeer, S.
Summary: The free radical scavenging activity (RSA) of Nigella sativa extract and its efficiency for cryopreservation of buffalo spermatozoa was investigated. In experiment 1, Nigella sativa extract was prepared and evaluated for RSA using 2, 2‐diphenyl‐1‐picrylhydrazyl assay. The results showed increased pattern of RSA at 1%–5% of Nigella sativa extract. In experiment 2, buffalo semen from three bulls (24 ejaculates) was incubated at 0%, 0.1%, 0.3%, 0.5%, 1%, 1.5%, 2%, 3%, 4%, 5% and 6% extract to assess in vitro tolerability to Nigella sativa in terms of progressive motility (PM). Buffalo spermatozoa showed tolerance to all levels; rather, sperm PM was increased at 1%–4% extract. In experiment 3, semen from three bulls (24 ejaculates) was cryopreserved with 0%, 1%, 2%, 3%, 4% and 5% of Nigella sativa extract. Sperm PM and plasma membrane integrity (PMI) were evaluated after dilution and cooling, while PM, PMI, viability and DNA integrity were evaluated after thawing. Nigella sativa extract at 4% in extender improved ( p < .05) post‐dilution, post‐cooling and post‐thaw sperm quality. In conclusion, Nigella sativa extract at all concentrations (1%–6%) showed antioxidant activity and its supplementation at 4% in extender improved buffalo sperm quality at all stages of cryopreservation.